2017
DOI: 10.5799/jcei.328748
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Content, Antioxidant and Cyto-/Genotoxic Activities of Pelargonium Quercetorum Agnew in Human Breast Cancer Cells

Abstract: Because the current cancer treatment success rate is not sufficient, plants have been gaining importance as a possible source for anti-cancer compounds. This study aimed to investigate both the genotoxic and cytotoxic activities of methanol extracts of Pelargonium quercetorum Agnew (P. quercetorum), which is traditionally used for its antihelminthic activity, but has not yet been studied for its effect in breast cancer cells. Methods: In this study, the cyto-genotoxic activities of methanol extracts of Pelargo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Basri et al revealed that low doses of acetone extract from stem bark of C. odontophyllum containing polyphenols showed significant DNA damage in HCT 116 cells [ 41 ]. Similarly Arı et al note that phenolic extract from Pelargonium quercetorum exerted genotoxic activity at relatively low doses in human breast cancer cells (MCF-7 and MDA-MB-231) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basri et al revealed that low doses of acetone extract from stem bark of C. odontophyllum containing polyphenols showed significant DNA damage in HCT 116 cells [ 41 ]. Similarly Arı et al note that phenolic extract from Pelargonium quercetorum exerted genotoxic activity at relatively low doses in human breast cancer cells (MCF-7 and MDA-MB-231) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a prostate tumor model, aggressive tumors established in NKG2D-deficient mice showed more prominent levels of NKG2D ligands compared with similar tumors in wild-type mice, indicating a lack of selective pressure by NKG2D-mediated responses. [21][22][23][24] Other reports delivered proof for the importance of NKG2D in NK cell growth and suggested that the lack of the NKG2D resulted in stunted proliferation of NK cells, and further reinforced their susceptibilities to apoptosis. 25…”
Section: Nk Cell-med Iated Immunosurveill An Ce Of C An Cermentioning
confidence: 99%
“…Although there are limited studies on this traditionally used plant, it has been shown to cause apoptosis in lung and breast cancer cell lines. In a previous study, it was proved by us that it exhibits antioxidant activity [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…endlicherianum from the Geraniaceae family have strong antimicrobial activity [20,21]. Besides, the strong effects of P. quercetorum and different Pelargonium species on cancer cell lines led us to evaluate the effects of nanoparticles synthesized by P. quercetorum [17,18,22]. For this reason, the biosynthesis of AgNPs was reported for the first time herein using different extracts that were obtained directly from the P. quercetorum plant.…”
Section: Introductionmentioning
confidence: 99%